Relasi Bisnis dan Politik di Indonesia Dalam Konteks Isu Kontemporer: Dampak, Tantangan, dan Implikasinya - Siregar, Agatha Cristy; Mawartina, Junita; Nursuhayla, Risma; Manurung, Kevin Immanuel (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The relationship between business and politics in Indonesia has a long and complex history that affects various aspects of social and economic life. This journal explores this relationship with a focus on contemporary issues such as corruption, economic policy, and environmental regulation. Amid rapid political and economic changes, the interaction between the business and political sectors often catalyzes policies that benefit certain interests, frequently at the expense of public interests. Through literature analysis and case studies, this journal aims to identify the impacts of corruption involving entrepreneurs and public officials, challenges in forming fair economic policies, and the implications of business lobbying on environmental regulation. The study finds that corruption undermines public trust and hinders economic growth, economic policies often favor large corporations over small and medium enterprises, and environmental regulations are frequently weakened by the influence of big business. The conclusions and recommendations provided are expected to offer new insights for researchers, policymakers, and the general public in efforts to enhance transparency and accountability in the interaction between business and politics in Indonesia.